2020
DOI: 10.3390/e22101115
|View full text |Cite
|
Sign up to set email alerts
|

Non-Extensive Statistical Analysis of Acoustic Emissions Recorded in Marble and Cement Mortar Specimens Under Mechanical Load Until Fracture

Abstract: Non-extensive statistical mechanics (NESM), which is a generalization of the traditionalBoltzmann-Gibbs statistics, constitutes a theoretical and analytical tool for investigating theirreversible damage evolution processes and fracture mechanisms occurring when materials aresubjected to mechanical loading. In this study, NESM is used for the analysis of the acousticemission (AE) events recorded when marble and cement mortar specimens were subjected tomechanical loading until fracture. In total, AE data origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…, based on Equation 7, obeys a q-exponential distribution proposed by ref [36] for AE data recorded from basalt specimens subjected to mechanical loading until fracture and verified in the cases of AE data recorded from mechanically loaded marble, sandstone and cement mortar specimens [37][38][39][40][41][42]:…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…, based on Equation 7, obeys a q-exponential distribution proposed by ref [36] for AE data recorded from basalt specimens subjected to mechanical loading until fracture and verified in the cases of AE data recorded from mechanically loaded marble, sandstone and cement mortar specimens [37][38][39][40][41][42]:…”
Section: Resultsmentioning
confidence: 77%
“…In the case of sub-additivity when 1 q > , a power law tail appears, whereas in the case of super-additivity when 0 1 q < < the q-exponential function presents a cut-off [26,27]. According to refs [36][37][38][39][40][41][42], the quantity that should be compared with the distribution the system under study is not the original ( )…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that acoustic emission (AE) signal analysis is a promising non-destructive technique for studying failure in concrete, e.g., within non-extensive statistical mechanics framework [ 4 , 5 , 6 ], damage localization in composite structures [ 7 , 8 ] and for damage monitoring in FRP materials [ 9 , 10 ]. When damage occurs in FRP materials, the sudden change in stress produces AE signal.…”
Section: Introductionmentioning
confidence: 99%